Mufasa, the lion king [compact disc] - Miranda, Lin-Manuel, 1980-; Miranda, Lin-Manuel, 1980-; M, Lebo (Walt Disney Records, 2024)
Immerse yourself in the captivating world of Disney's "Mufasa, The Lion King," featuring the original songs by the acclaimed Lin-Manuel Miranda and Lebo M. Relive the magic of this timeless tale through the mesmerizing melodies that transport you to the heart of the Pride Lands.